IMPROVING STUDENTS’ WRITING SKILL BY USING INQUIRY TECHNIQUE AT THE EIGHTH GRADE STUDENTS OF MTS NEGERI 2 PALEMBANG - Akhirotul Faizatin Nisa (Edukasi, 2015)
The objectives of this study was to find out whether or not there was any significant difference on students’ writing achievement between the students who are taught by using inquiry technique and those who are taught by using teachers’ technique at the eighth grade students of MTs Negeri 2 Palembang. This research was conducted through quasi-experimental method and used nonequivalent control group design. The population was 287 students of the eighth grade of MTs Negeri 2 Palembang in the academic year 2013/2014. Sixty two students were chosen as the sample by using convenience sampling technique. The sample were assigned into two groups; the experimental group and the control group. Each group consisted of thirty one students. The data were obtained by written test. A test was given both to the experimental group and control group but only one group given treatment. The result of the test was analyzed by means of  SPSS 16. Based on the result of  the data analysis that is the result of hypothesis testing using independent sample t-test, the significant difference was found the p-output (0.000) lower  than 0.05. It means that, there was a significant difference between students’ pretest and posttest scores in experimental group taught using inquiry technique. Therefore, it can be concluded that inquiry technique was significantly improved. The writer also found that most of the students of both groups  made a good writing improvement. However, there were still some students who were poor in writing skill.